Social networks, job search methods and reservation wages: Evidence for Germany - Marco Caliendo; Ricarda Schmidl; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2010)
In this paper we analyze the relationship between social networks and the job search behavior of unemployed individuals. It is believed that networks convey useful information in the job search process such that individuals with larger networks should experience a higher productivity of informal search. Hence, job search theory suggests that individuals with larger networks use informal search channels more often and substitute from formal to informal search. Due to the increase in search productivity, it is also likely that individuals set higher reservation wages. We analyze these relations using a novel data set of unemployed individuals in Germany containing extensive information on job search behavior and direct measures for the social network of individuals. Our findings confirm theoretical expectations. Individuals with larger networks use informal search channels more often and shift from formal to informal search. We find that informal search is mainly considered a substitute for passive, less cost intensive search channels. In addition to that, we find evidence for a positive relationship between the network size and reservation wages.
Keywords: J64; 330; job search behavior; unemployment; social networks